Mexico's sugar policy. - ALBERTOS CAMARA, Rudy O. (1992)
Presents the strategies undertaken by the Mexican government to modernize the country's sugar industry. Includes the main problems encountered, the results achieved, and activities necessary to maintain the new structures.